Low Code for Smart Software Development - Cabot, Jordi; Clariso, Robert; Menzies, Tim (IEEE software, 2023)
The more we know about patterns in code, the better we can support those patterns. In this article, Jordi Cabot and Robert Claris ´o discuss the promise and perils of AI enhanced low-code environments that allow programmers and non=programmers alike to quickly deliver software solutions. They offer a “wish list” that outlines what developers need to watch for in low-code tools for smart software. Got anything else you want to say about SE+AI? For SE+AI applications, you have a surprising result or industrial experience? Something that challenges decades of conventional thinking in software engineering? If so, email a one paragraph synopsis to tim@menzies.us (use the subject line “SE for AI: Idea: [your idea]”). If that looks interesting, I’ll ask you to submit a 1,000- to 2,400-word article (where each graph, table, or figure is worth 250 words) for review for IEEE Software. Note: Heresies are more than welcome (if supported by well-reasoned industrial experiences, case studies, or other empirical results).—Tim Menzies